The Chest Physiotherapy to Manage Respiratory Rate In Patients with Bronchopneumonia: A Literature Review: Indonesia - Bisma Yudha, Magenda; Wardoyo, Eko (Global Indonesia Health Care (GOICARE), 2023)
Purpose: Knowing the application of chest physiotherapy techniques can manage respiratory rates in children with bronchopneumonia. Methods: This review uses the literature review method. Searches were conducted in PubMed, Garuda, and Google Scholar. The search strategy used keywords with